Cluster nursing management for a patient with lumbar disc herniation induced low back pain combined with hyperglycemia (1例腰椎间盘突出症腰痛合并血糖升高患者的集束化护理管理) - SHEN Hui (申慧); DONG Wei (董伟); WANG Cuiying (王翠英); ZHANG Xiangju (张香菊); LIU Tianhao (刘天浩); CHANG Shilei (常石磊); XIE Yingdong (解英东); SUN Lei (孙磊) (Association of Integrative Nursing, 2023)
This paper summarized the cluster nursing management for a patient with lumbar disc herniation induced low back pain combined with hyperglycemia. The patient received lumbar paravertebral nerve block, and was diagnosed with hyperglycemia before the surgery. Based on the nursing risk assessment, the cluster nursing management including perioperative blood sugar monitoring, postoperative observation and health education were carried out to ensure the surgical safety and improve the prognosis and postoperative rehabilitation of the patient. (本文总结1例腰椎间盘突出症腰痛合并血糖升高患者的集束化护理管理体会。患者接受椎旁神经单次阻滞镇痛治疗, 治疗前发现血糖升高。在完善护理评估的基础上, 加强围手术期血糖监测、术后观察和健康宣教, 旨在确保患者围手术期安全, 改善预后, 促进康复。)